KARAKTERISTIK PENDERITA DIABETES MELLITUS DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT VITA INSANI PEMATANGSIANTAR TAHUN 2011 - merlyn sinaga; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Diabetes Mellitus (DM) is a chronic degenerative disease with a prevalence continue to increase. World Health Organization (WHO, 2003) estimates that 5,1% of the people in the world with diabetes aged 20-79 years. Based on data Riskesdas 2007, the national prevalence of diabetes based on blood glucose measurements population aged > 15 years residing in urban areas was 5,7%. The objective of this research to know the characteristics of patients DM admitted to the Pematangsiantar Vita Insani Hospital in 2011. This research is descriptive study with case series design. The population in this study was 123 people, sample was the same as the population (Total Sampling). The results showed the proportion of patients with complications of DM was highest in the age group 51-60 years (33,3%), female (65,0%), Batak (74,8%), Christian Protestant (56,9% ), senior high school education (32,7%),housewife (28,5%), out of Pematangsiantar (52,8%), type 2 diabetes mellitus (99,2%), Gastritis complication (32,5%), chronic complications (89,4%), Hypoglycemic oral medicine (63,4%), own expense (86,2%), average length of stay (5 days), and becoming outpatient (78,9%). According to statistic, there was no difference between age based on category complication (p=0,501)and there was difference betwen average lenght of stay based on expense surces (p=0,000). It is suggested to the Vita Insani Hospital can give information to DM patient with discharge and becoming out patient to control blood glucose regularly, adopting a healthy lifestyle and taking medication regularly so that blood sugar levels can be controlled. Keywords:Characteristic, Diabetes Mellitus with complication